“Escrevi sobre diversos assuntos, mas mantive os mesmos princípios”: a linguagem paradoxal como construção crítica no pensamento de Jean-Jacques Rousseau - Barbosa, Barbara Rodrigues (2016)
This research’s investigative motto is the Jean-Jacques Rousseau’s adage in his book Emile, or On the Education (1762), to know, “whatever they may say I would rather be a man of paradoxes than a man of prejudices” (ROUSSEAU, 2004, p.96). We take from the analysis of some of his works, as in, Discourse About the Science and the Arts (1750) and the Narcissus’ Preface (1752), just as the polemics about his dircours. It’s about, above all, of clarifying that in the study we look to the paradox as a philosophical concept, videlicet, to understand the paradox as a line of thought capable of understanding the received opinions and reorganize then. Other authors have already concerned about paradox in some studies and in their works2, but with no intention to run out of it, or to give a definitively answer, this rummage comes in an attempt to sense the presence of the paradox in the Discourse About the Science and the Arts and notice what is the function of this Jean-Jacques’s line of thought and if it can be recognized as a critical language